Targeting the MAPK/ERK and PI3K/AKT Signaling Pathways Affects NRF2, Trx and GSH Antioxidant Systems in Leukemia Cells - Ewa Jasek-Gajda; Halina Jurkowska; Małgorzata Jasińska; Grzegorz J. Lis (MDPI AG, 2020)
The mitogen-activated protein kinase (MAPK)/extracellular signal kinase (ERK) and phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) signal transduction pathways have been implicated in the pathogenesis of leukemia. The aim of this study was to investigate the effect of the combination of ERK1/2 inhibitor AZD0364 and PI3K inhibitor ZSTK474 on acute lymphoblastic leukemia (ALL) REH, MOLT-4, acute myeloid leukemia (AML) MOLM-14, and chronic myeloid leukemia (CML) K562 cell lines. To evaluate the interactions of the drugs, cells were treated for 48 h with AZD0364 or ZSTK474 alone and in combination at fixed ratios. The combinatorial effects of both inhibitors were synergistic over a wide range of concentrations in REH, MOLT-4, and MOLM-14 cell lines. However, in K562 cells, the effects were found to be antagonistic. Furthermore, AZD0364 and ZSTK474 significantly decreased both ERK1/2 and AKT activation in REH, MOLT-4, and MOLM-14 cells. The results showed that incubation with both AZD0364 and ZSTK474 inhibited cell viability, increased reactive oxygen species (ROS) production, and induced apoptosis in leukemia cells. We observed that combined treatment with AZD0364 and ZSTK474 affected nuclear factor-κB (NF-κB) and antioxidant protein levels: NF-E2-related factor 2 (NRF2), heme oxygenase-1 (HO-1), thioredoxin (Trx), thioredoxin reductase (TrxR), and the reduced glutathione/oxidized glutathione (GSH/GSSG) ratio. These effects were accompanied with decreased antiapoptotic survivin protein level. However, distinct cell line dependent effects were observed. In conclusion, the combination of AZD0364 and ZSTK474 can exert a synergistic anticancer effect in ALL and AML cells, which is associated with the induction of oxidative stress and the involvement of cellular antioxidant defense mechanisms.